Activation of Nuclear Factor Erythroid 2-Related Factor 2 Transcriptionally Upregulates Ectonucleotide Pyrophosphatase/Phosphodiesterase 1 Expression and Inhibits Ectopic Calcification in Mice - Ida Tomomi; Hiroyuki Kanzaki; Miho Shimoyama; Syunnosuke Tohyama; Misao Ishikawa; Yuta Katsumata; Chihiro Arai; Satoshi Wada; Shugo Manase; Hiroshi Tomonari (MDPI AG, 2024)
Calcification plays a key role in biological processes, and breakdown of the regulatory mechanism results in a pathological state such as ectopic calcification. We hypothesized that ENPP1, the enzyme that produces the calcification inhibitor pyrophosphate, is transcriptionally regulated by Nrf2, and that Nrf2 activation augments ENPP1 expression to inhibit ectopic calcification. Cell culture experiments were performed using mouse osteoblastic cell line MC3T3-E1. Nrf2 was activated by 5-aminolevulinic acid and sodium ferrous citrate. Nrf2 overexpression was induced by the transient transfection of an Nrf2 expression plasmid. ENPP1 expression was monitored by real-time RT-PCR. Because the promoter region of ENPP1 contains several Nrf2-binding sites, chromatin immunoprecipitation using an anti-Nrf2 antibody followed by real-time PCR (ChIP-qPCR) was performed. The relationship between Nrf2 activation and osteoblastic differentiation was examined by alkaline phosphatase (ALP) and Alizarin red staining. We used mice with a hypomorphic mutation in ENPP1 (ttw mice) to analyze whether Nrf2 activation inhibits ectopic calcification. Nrf2 and Nrf2 overexpression augmented ENPP1 expression and inhibited osteoblastic differentiation, as indicated by ALP expression and calcium deposits. ChIP-qPCR showed that some putative Nrf2-binding sites in the ENPP1 promoter region were bound by Nrf2. Nrf2 activation inhibited ectopic calcification in mice. ENPP1 gene expression was transcriptionally regulated by Nrf2, and Nrf2 activation augmented ENPP1 expression, leading to the attenuation of osteoblastic differentiation and ectopic calcification in vitro and in vivo. Nrf2 activation has a therapeutic potential for preventing ectopic calcification.